Developing Halal edugastronomy tourism framework based on Maqasid shariah among Muslim local food providers in Malaysia: A conceptual paper - Wan Nasri, Che Mat Safiee; Saffinee, Siti Syahirah; Jamaludin, Mohammad Aizat; Mohd Noor, Khairuneezam; Mohd Salleh, Mohd Mahyeddin; Mohd, Nur Shuhadah (Rynnye Lyan Resources, 2025)
The diversity of culture in Malaysia has opened tourism opportunities mainly related to local gastronomy components that can be inserted from the Halalan-Toyyiban concept. The culinary knowledge from Muslim Local Food Providers (MLFPs) will help to interest the tourists in experiencing gastronomic satisfaction. However, a lack of awareness among MLFPs in practising Halalan-Toyyiban in gastronomy tourism will decline the actual quality and food standards. This paper aimed to develop a new framework regarding Halal Edugastronomy Tourism (HEGTo) based on Maqasid Shariah to preserve and promote cultural diversity in Malaysia and draw attraction from Muslim tourists. The paper used qualitative data from previous studies about MLFPs with gastronomy, the Halalan-Toyyiban concept, the approaches in edugastronomy, the tourism aspect, and the role of Maqasid Shariah in HEGTo. A comprehensive HEGTo framework from the understanding of principles of halal gastronomy tourism, as well as Maqasid Shariah, will be shown as a result. This paper provides an idea to improve current methods and promote cultural variety, sustainable tourism, and overall benefits for society and the national economy.